2016
DOI: 10.1038/nchembio.2029
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of polysaccharide cleavage by lytic polysaccharide monooxygenases

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
515
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(567 citation statements)
references
References 51 publications
40
515
2
1
Order By: Relevance
“…The flat catalytic binding surfaces of LPMOs are well suited to bind polysaccharides and disrupt glycosidic linkages (38). However, a few LPMOs are characterized to bind and cleave shorter cellooligosaccharides such as cellohexaose and celloheptaose (39) whereas oligosaccharides smaller than cellohexaose cannot be accommodated in LPMO flat binding site (40). This suggests that LPMO bind and cleave higher oligomers and crystalline surfaces, thereby acting as first wave of attack in disintegration of recalcitrant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The flat catalytic binding surfaces of LPMOs are well suited to bind polysaccharides and disrupt glycosidic linkages (38). However, a few LPMOs are characterized to bind and cleave shorter cellooligosaccharides such as cellohexaose and celloheptaose (39) whereas oligosaccharides smaller than cellohexaose cannot be accommodated in LPMO flat binding site (40). This suggests that LPMO bind and cleave higher oligomers and crystalline surfaces, thereby acting as first wave of attack in disintegration of recalcitrant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, LPMOs have been at the centre of much research attention, with several recent reviews providing insights into the published data and the possible mechanisms of action of LPMOs [7][8][9][10][11] , including a very recent structure of an LPMO in association with an oligosaccharide substrate 12 . LPMOs use an oxidative mechanism to introduce chain breaks into polysaccharides thereby augmenting the activity of classical glycoside hydrolases, as shown by Vaaje Kolstad et al 13 in their breakthrough study of CBP21 (chitin-binding protein 21) from Serratia marcescens.…”
Section: Introductionmentioning
confidence: 99%
“…The utmost levels of total sugar content were found for treatments 21/15/9ºC and 15/9/6ºC, both with a significant difference to the lower level at 21ºC [42]. Shattuck et al (1991a) reported that a low growth temperature (0-12ºC) for 11 days before harvesting considerably increased the total sugar content [39][40][41][42][43]. Comparable results have also been reported by Davik (1992) and Shattuck et al (1991a).…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, Molmann et al (2015) found no significant differences in vitamin C content between broccoli grown at 12ºC and 18ºC [41]. The utmost levels of total sugar content were found for treatments 21/15/9ºC and 15/9/6ºC, both with a significant difference to the lower level at 21ºC [42]. Shattuck et al (1991a) reported that a low growth temperature (0-12ºC) for 11 days before harvesting considerably increased the total sugar content [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 97%